Paket Informasi Obat-Obat Herbal Berbasis Lokal Konten di Kecamatan Koto Tangah Kota Padang - Ayumanda, Dinda; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
Abstract This research is about the writing of a package book containing information of local-bared content herbal medicines. The purpose of this research is to explain kinds of Minangkabau herbal local plants and their benefits. Further, it will describe the processes of writing the book. This research is conducted by using descriptive method and the data are collacted through observation and interview toward local community who own herbal plants in RT 02/RW 11 Dadok Tunggul Hitam and Lubuk Minturun Agro-tourism located in Koto Tangah sub-discrict in Padang. After the data are analyzed, it can be conducted that there are some stages and designs in writing the book. The stage are: (a) identifying the reader needs; (b) set topic of information; (c) collecting informations; (d) evaluating the information validity; (e) analyzing, selecting, and eztracting the information; (f) repackaging information; and (g) defining the readers. The designs are: (1) composing the framework of writing; (2) making cover; (3) making introduction; (4) making table of contents; (5) the content of the book; (6) closing; and (7) back cover.Keywords: information, package of information, and herbal medicine